KEBIJAKAN PEMERINTAH INDONESIA DALAM MENGATASI HAMBATAN FREE TRADE ZONE DI BATAM (STUDI KASUS : HUTAN LINDUNG) - Dewi Fatimah Azzahra; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine how government policies in overcoming the barriers that exist in Batam Batam as a region in realizing a Free Trade Zone (FTZ). The author will focus on one of these obstacles is the problem of protected forest areas in Batam. Free Trade Zone (FTZ) is a region or zone that is getting a policy in the form of facilities or free up some kind of object of trade of some customs rules, including taxes and charges. The method used in this study is a qualitative research method with Study Library (Library Research) technique. This study shows that there are several government policies to overcome the obstacles that exist in Batam Batam as a region in realizing a Free Trade Zone (FTZ). Such as, (1) the Government Regulation (PP) No. 46 of 2007, (2) SK 76/MenLHK-II/2015, and then through (3) And the cooperation between Indonesia and Singapore. Which of these policies have an alternative solution is required.Keywords: Batam, Policy, Free Trade Zone (FTZ), Protected Forest.